Yiqi-Bushen-Tiaozhi Recipe Attenuated High-Fat and High-Fructose Diet Induced Nonalcoholic Steatohepatitis in Mice via Gut Microbiota - Yan, Junbin; Nie, Yunmeng; Liu, Yuan; Li, Jingya; Wu, Liyan; Chen, Zhiyun; He, Beihui (Frontiers in Cellular and Infection Microbiology, 2022)
Aim: To investigate the treating effect of Yiqi-Bushen-Tiaozhi (YBT) recipe on nonalcoholic steatohepatitis (NASH) mice, determine whether the outcome was associated with gut microbiota, and clarify the regulating mechanism. Methods: NASH mice were induced by high-fat and high-fructose diets (HFFD). In the 5th week, mice in the YBT group were orally administrated YBT (22.12g·kg-1·d-1) daily for 12 weeks. Fresh stool of mice was collected at the 16th week for fecal 16S rDNA analysis. Hepatic pathology and biochemical indicators were used to reflect the improvement of YBT on hepatic inflammation and lipid metabolism in NASH mice. Results: Results of the pathological and biochemical index showed that YBT could improve NASH mice. Compared with improving inflammation and hepatocyte damage, YBT may be more focused on enhancing metabolic disorders in mice, such as increasing HDL-c level. The diversity and richness of the gut microbiota of NASH mice induced by HFFD are significantly different from the normal control (NC) group. After YBT treatment, the diversity and richness of the mice microbiota will be increased to similar NC mice. Intestinimonas, Acetatifactor, Alistipes, Intestinimonas, Acetatifactor, and Alistipes have the most significant changes in the class level. PICRUSt analysis was performed for predicting genomic functions based on the 16S rDNA results and reference sequencing. The efficacy of YBT in the treatment of NASH can be achieved by regulating the diversity and richness of gut microbiota. PICRUSt analysis results showed that the most relevant function of the microbiota construction variations is α- Linolenic acid (ALA) metabolism. Conclusion: YBT could treat NASH mice by improving the diversity and richness of gut microbiota and further the improvement of ALA metabolism.